2014
DOI: 10.1530/erc-14-0254
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA hypermethylation of SDHC: a novel mechanism of tumor development in Carney triad

Abstract: Carney triad (CT) is a rare condition with synchronous or metachronous occurrence of gastrointestinal stromal tumors (GISTs), paragangliomas (PGLs), and pulmonary chondromas in a patient. In contrast to Carney–Stratakis syndrome (CSS) and familial PGL syndromes, no germline or somatic mutations in the succinate dehydrogenase (SDH) complex subunits A, B, C, or D have been found in most tumors and/or patients with CT. Nonetheless, the tumors arising among patients with CT, CSS, or familial PGL share a similar mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
2
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(138 citation statements)
references
References 29 publications
4
124
2
8
Order By: Relevance
“…Killian et al then confirmed these results, performing genomewide DNA methylation profiling and demonstrating that six of the 15 Carney triad patients had SDHC epimutation (Haller et al 2014, Killian et al 2014. Finally, very recently, SDHx mutations were found in patients with Carney triad, suggesting that the various SDH-deficient syndromes overlap significantly (Boikos et al 2016b).…”
Section: Carney Triadmentioning
confidence: 86%
“…Killian et al then confirmed these results, performing genomewide DNA methylation profiling and demonstrating that six of the 15 Carney triad patients had SDHC epimutation (Haller et al 2014, Killian et al 2014. Finally, very recently, SDHx mutations were found in patients with Carney triad, suggesting that the various SDH-deficient syndromes overlap significantly (Boikos et al 2016b).…”
Section: Carney Triadmentioning
confidence: 86%
“…While the findings described herein by Haller et al (2014) are the first to definitively link SDHC genetic dysregulation to tumorigenesis in Carney triad, earlier work from the Stratakis group had suggested that SDHC might have a role to play. Matyakhina et al (2007) demonstrated that among 41 tumors in 37 cases of Carney triad, the most frequent recurrent genetic abnormality was a large-scale copy number loss that included the locus for SDHC (chromosome 1q21-q23.3).…”
Section: Succinate Dehydrogenase Gene Dysregulation Is Instrumental Imentioning
confidence: 57%
“…This epigenetic silencing profile of SDHB, along with SDHB copy number changes and loss of SDHB staining in Carney triad tumors implies that SDHx-related abnormalities might be somewhat more generalized than SDHC alone (Matyakhina et al 2007, Haller et al 2014. Study of more Carney triad tumors will help to define the relative variability or specificity of hypermethylation patterns in SDHC and SDHB.…”
Section: Succinate Dehydrogenase Gene Dysregulation Is Instrumental Imentioning
confidence: 95%
See 1 more Smart Citation
“…Nonetheless, the GISTs from Carney triad display loss of immunoreactivity for SDHB (39). This finding can be explained by SDHx somatic losses or by epigenetic silencing of SDHC promoter (40). SDH-deficient GISTs account for 5-7.5% of all GISTs.…”
Section: Gastrointestinal Stromal Tumors (Gists)mentioning
confidence: 99%